Implementación de una red lan con la utilización de cableado estructurado basado en las normas internacionales ANSI /TIA /EIA 568-B, en el Laboratorio de Investigación de Ingeniería de Software en la Universidad Técnica De Cotopaxi, Extensión La Maná, en el año 2017" - Cedeño Tumbaco, Lidia Liliana (2017)
This project aims to implement a LAN network using structured cabling based on international standards ANSI/TIA/EIA 568-B, for effect, a technical study was carried out to determine the resources, equipment and materials necessary for the structuring of the local network, in the same way the methods, techniques and research tools will be used to collect the information concerning the variables of the study object , in order to have a clearer idea of the type of network that will be structured according to the needs of the laboratory, seeking to equip technological tools for the practice of students of the career of engineering in computer science and computer systems. One of the aspects that organizations need to take into account is taking timely actions in the technological field that allow them to be more efficient and competitive, acquiring equipment and communication systems that are an important contribution to the development of them. For the accomplishment of this work it was investigated on the benefits generated by the implementation of a LAN network of structured cabling, taking into account an appropriate analysis and design, obtaining all the physical details that include, furniture, work area, cabling standards and installation specifications, in this way we will optimize the correct operation of the data transmission in the laboratory of Software engineering research at the Technical University of Cotopaxi- La Maná.